MATERIALISM IN FRANCES HODGSON BURNETT’S A LITTLE PRINCESS - Bakary, Heidy; Oroh, Elisabeth; Mamentu , Agustine C. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
Everyone has a tendency to prioritize material wealth and comfort over spiritual principles. The most crucial aspect of life is having money and possessions. The purpose of this study is expose the materialism that the A Little Princess potrays. The study used qualitative research, which uses words rather than numbers to present the data. Data analysis employs a mimetic approach. The findings of this study demonstrate that materialism began during the Victorian era. The novel’s potrayal of Miss Minchin as a materialistic individual was made clear through aterialism. With the materialistic nature possessed by Miss Minchin, she will do anything so that her wishes are fulfilled without caring about others who feel tortured and hurt due to her actions.